2018
DOI: 10.1126/sciadv.aar3219
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure, osteopontin, and mechanical properties of calcitic avian eggshell

Abstract: The biomineral phase of avian eggshell is characterized at the nanostructure scale and correlated with functional properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 61 publications
12
89
0
Order By: Relevance
“…In some parts, however, the extinction pattern is irregular. It should be noted that the extinction pattern is similar to the grain shape of calcite detected by EBSD analysis (Athanasiadou et al, 2018; see EBSD observation below) that was also reported in nonavian dinosaur eggshell fossils (e.g., see Moreno-Azanza et al, 2013, Figures 1, 3 for cases of Trigonoolithus amoae and cf. Maiasaura eggshell) and extant gecko eggshells (Choi et al, 2018, Figures 4, 9).…”
Section: Polarized Light Microscopysupporting
confidence: 78%
“…In some parts, however, the extinction pattern is irregular. It should be noted that the extinction pattern is similar to the grain shape of calcite detected by EBSD analysis (Athanasiadou et al, 2018; see EBSD observation below) that was also reported in nonavian dinosaur eggshell fossils (e.g., see Moreno-Azanza et al, 2013, Figures 1, 3 for cases of Trigonoolithus amoae and cf. Maiasaura eggshell) and extant gecko eggshells (Choi et al, 2018, Figures 4, 9).…”
Section: Polarized Light Microscopysupporting
confidence: 78%
“…In general, vertebrates utilize calcium phosphate as the building blocks of their internal skeleton whereas invertebrates use calcium carbonate for their shell construction (Cusack & Freer ; Cusack ; Athanasiadou et al . ). Biomineralization studies using EBSD have been mainly concentrated on invertebrates such as bivalves, brachiopods, corals and trilobites (Cusack , and references therein).…”
Section: The Ebsd Mapping Images Of Dinosaur Eggshell Available In Thmentioning
confidence: 97%
“…Although the CaO catalyst is obtained by calcining eggshells, which inevitably generates CO 2 , there is no net increase in CO 2 greenhouse gas (Figure S3, Supporting Information). Taking into account the entire carbon cycle, the CaCO 3 in the eggshell originated from the reaction of Ca ions and carbonates (CO 3 ) obtained from CO 2 in the air …”
Section: Study Of the Graphene Deposition Mechanismmentioning
confidence: 99%